Circular RNA as an Additional Player in the Conflicts Between the Host and the Virus - Choudhary, Aditi; Madbhagat, Pratibha; Sreepadmanabh, M.; Bhardwaj, Vipin; Chande, Ajit (Frontiers in Immunology, 2021)
Circular RNA (circRNA), a relatively new member of the non-coding RNA family, has spurred great interest among researchers following its discovery as a ubiquitous class within the RNA world. Rapid progress in circRNA biology with a plethora of diverse roles- including regulation of gene expression, probable coding potential, competing interactions with proteins and microRNAs- being attributed to circRNAs has been emphasized in various pathological conditions. Emerging evidence suggests that circRNAs also function in viral infections. The deregulation of circRNAs during viral infection has prompted investigations into the possibilities of circRNA as a competing endogenous RNA (ceRNA) that modulates response to infection. Recently, viruses have been shown to encode circRNAs with proviral functions, providing a strong impetus for focused efforts to elucidate the networks coaxed by circRNAs during infection. This review elaborates on recent insights gained on the roles of circRNAs during virus infection and immunity.